2012
DOI: 10.4100/jhse.2012.73.09
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of anthropometric characteristics with physical fitness tests in Indian professional hockey players

Abstract: Sharma A, Tripathi V, Koley S. Correlations of anthropometric characteristics with physical fitness tests in Indian professional hockey players. J. Hum. Sport Exerc. Vol. 7, No. 3, pp. 698-705, 2012. The purpose of this study was to investigate the correlations of anthropometric characteristics with isotonic strength (handgrip strength), lower limb power, aerobic strength, and skill tests in purposely selected 60 Indian professional male hockey players of different levels players (35 national and 25 state leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
4
16
0
5
Order By: Relevance
“…The present hockey players showed much lower BF% value according to different positions than earlier reported data of national players (Koley and Vashisth, 2014: goalkeepers 17.9 ±3.8%, defenders 14.8 ±2.7%, midfielders 16.9 ±4.7%, forwards 15.4 ±2.5%). Although, in the present study, no differences were observed in BF% among the assessed positions however, in accordance with previous study of Sharma et al (2012), goalkeepers showed a higher BMI, greater BF% and muscle mass in contrast to other positions. Lower value in fat% and muscle mass of present midfielders/forwards represents developed skill in aerobic and anaerobic system and particularly a light, reactive body which was highlighted in a previous study (Malhotra et al, 1974).…”
Section: Discussionsupporting
confidence: 91%
“…The present hockey players showed much lower BF% value according to different positions than earlier reported data of national players (Koley and Vashisth, 2014: goalkeepers 17.9 ±3.8%, defenders 14.8 ±2.7%, midfielders 16.9 ±4.7%, forwards 15.4 ±2.5%). Although, in the present study, no differences were observed in BF% among the assessed positions however, in accordance with previous study of Sharma et al (2012), goalkeepers showed a higher BMI, greater BF% and muscle mass in contrast to other positions. Lower value in fat% and muscle mass of present midfielders/forwards represents developed skill in aerobic and anaerobic system and particularly a light, reactive body which was highlighted in a previous study (Malhotra et al, 1974).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly research in field hockey, players' game configurations and outcome performance were affected by body composition, somatayping and physical motor-ability. Apart from tactical decision making and skill execution , anthropometric of a lean body, sprinting capability of 50 -60 meters, cardiovascular fitness (V0 2 max ), agility, leg power, speed, strength and anaerobic capacity are the characteristics that significantly influence game configurations and performances in the field hockey (Mannal, Khanna, Dhara, 2004;Sharma, Tripathi, & Koley, 2012;Wassmer & Mookerjee, 2002). Hence TGfU practitioners dealing games coaching need to consider these attributes as it is crucial in game play such hockey.…”
Section: Introductionmentioning
confidence: 99%
“…In this sports activity, the players are to flex the trunk forward to the ground for the maximum groundwork and to cover a wider range [43]. Finally, the maximum strain of muscles specifically abdominal muscles, as well as back muscles, will be developed during the entire length of the game [44]. Therefore, the important findings of the current study present that the core muscle strength is highly demanded in the field hockey.…”
Section: Resultsmentioning
confidence: 91%